Posttraumatic Stress Symptom Severity and Functional Impairment in a Trauma-Exposed Sample: A Preliminary Examination into the Moderating Role of Valued Living - Donahue, John; Khan, Humama; Huggins, Jefferson; Marrow, Tykera (Elsevier, 2017)
Posttraumatic Stress Disorder (PTSD) is associated with functional impairment in social, occupational, and physical domains. Similar to other forms of psychopathology, research suggests the correlation between symptom severity and functional impairment is moderate and this relationship varies across studies. These findings suggest a continued need to identify variables that explain unique variance in functional outcomes over and above PTS symptomology, as well as those that moderate this association. One such variable may be valued living, a primary treatment target in contextual behavioral approaches such as Acceptance and Commitment Therapy (ACT). The present study sought to investigate the association between valued living, PTS symptomology, and functional impairment in a trauma-exposed sample, as well as the moderating effect of valued living in the relationship between symptom severity and functioning. Results confirmed valued living is associated with functional impairment after controlling for PTS symptom severity and other covariates, and valued living does moderate the link between symptoms and impairment in functioning. Findings highlight the importance of the interplay between valued living and symptomology in understanding impairment among trauma-exposed individuals.
Keywords: Valued living; Posttraumatic stress disorder; Functional impairment; Acceptance and commitment therapy